Inovasi Metode Gallery Walk pada Pembelajaran Online dengan Aplikasi Artsteps selama Pandemi Covid-19 - Heru Setiawan; Riandi Riandi; Bambang Supriatno (Asatiza: Jurnal Pendidikan, 2022)
The purpose of this study is to analyze students’ response of the Gallery Walk Method with the innovation of ArtSteps of Plant and Animal Classification and evaluate the obstacles in online learning during the Covid-19 pandemic. This research was conducted in grade X which consists of 15 students in Senior High School of Global Mandiri Jakarta. The instrument is the questionnaire and interviews. Based on the results of the questionnaire, we found that most students gave positive responses. More than three-quarters of students can understand the plant and animal classification material well, can express their creativity, and are more active during online learning. Students are also satisfied with their peers' presentations. According to the result of the Interview, the biggest challenge for the implementation is the internet network and the lack of real interaction with classmates. The recommendation is that students need to discuss each station for at least 15 minutes and twice in each station of Artsteps for more effectiveness.